Enhanced Performance of the Gorlov Hydrokinetic Turbine through Blade Profile Modification - Rendi, Rendi; Arifin, Jainal; Pauzan, Muhammad (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2024)
The Gorlov turbine is a widely used hydrokinetic turbine for household-scale hydroelectric power generation, known for its superior performance compared to other turbine types. Despite its high efficiency, the Gorlov turbine has a significant drawback: it cannot operate effectively at low water speeds due to its blade design, which relies solely on lift force. This study aims to address this limitation by modifying the blade profile to harness drag force in addition to lift force. The modified blade profile retains the original crescent shape while enhancing its design. For data validation, two models were created: the conventional Gorlov turbine and a modified version. Laboratory-scale tests were conducted using a water pump to simulate flow in an artificial channel, with water speeds ranging from 0.185 m/s to 0.225 m/s. Correlation regression analysis was employed to evaluate the experimental results and strengthen the reliability of the findings. The results indicate a correlation between changes in water flow speed and increases in turbine rotation, turbine torque, torque coefficient, and power coefficient. Specifically, the conventional Gorlov turbine exhibited an average torque of 0.014 Nm, a torque coefficient of 0.0209, and a power coefficient of 0.32. In contrast, the modified Gorlov turbine demonstrated an average torque of 0.016 Nm, a torque coefficient of 0.239, and a power coefficient of 0.308.